2017
DOI: 10.1371/journal.pone.0181765
|View full text |Cite
|
Sign up to set email alerts
|

Construction and characterization of the Korean whole saliva proteome to determine ethnic differences in human saliva proteome

Abstract: As the first step to discover protein disease biomarkers from saliva, global analyses of the saliva proteome have been carried out since the early 2000s, and more than 3,000 proteins have been identified in human saliva. Recently, ethnic differences in the human plasma proteome have been reported, but such corresponding studies on human saliva in this aspect have not been previously reported. Thus, here, in order to determine ethnic differences in the human saliva proteome, a Korean whole saliva (WS) proteome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Future studies including a larger breed representation in the various phylogenic groups and a larger number of dogs per breed will help answer this question. Interestingly, a recent study showed unique proteins in the saliva of Korean people when compared to a comprehensive database of human salivary proteins indicating ethnic differences in the human saliva proteome [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies including a larger breed representation in the various phylogenic groups and a larger number of dogs per breed will help answer this question. Interestingly, a recent study showed unique proteins in the saliva of Korean people when compared to a comprehensive database of human salivary proteins indicating ethnic differences in the human saliva proteome [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics. Numerous proteomic studies have provided evidence for the influence of ethnicity on protein expression (Cho et al, 2017;Kim et al, 2010;Nguyen et al, 2019). We are currently in what might be considered the ''golden age'' of proteomics, characterized by the creation of public proteomics databases, the development of structural analysis tools which predict variant effects, such as HUMA and PRIMO (Brown and Tastan Bishop, 2018;Hatherley et al, 2016), and the standardization of data submission under the Proteo-meXchange consortium (Vizcaíno et al, 2014 Egypt).…”
Section: Availability Of Human African Omics Datamentioning
confidence: 99%